Lack of association of genetic variants for diabetic retinopathy in Taiwanese patients with diabetic nephropathy. Issue 1 (20th January 2020) - Hsieh, Ai-Ru; Huang, Yu-Chuen; Yang, Ya-Fei; Lin, Hui-Ju; Lin, Jane-Ming; Chang, Ya-Wen; Wu, Chia-Ming; Liao, Wen-Ling; Tsai, Fuu-Jen
Abstract : Objective: Diabetic nephropathy (DN) and diabetic retinopathy (DR) comprise major microvascular complications of diabetes that occur with a high concordance rate in patients and are considered to potentially share pathogeneses. In this case-control study, we sought to investigate whether DR-related single nucleotide polymorphisms (SNPs) exert pleiotropic effects on renal function outcomes among patients with diabetes. Research design and methods: A total of 33 DR-related SNPs were identified by replicating published SNPs and via a genome-wide association study. Furthermore, we assessed the cumulative effects by creating a weighted genetic risk score and evaluated the discriminatory and prediction ability of these genetic variants using DN cases according to estimated glomerular filtration rate (eGFR) status along with a cohort with early renal functional decline (ERFD). Results: Multivariate logistic regression models revealed that the DR-related SNPs afforded no individual or cumulative genetic effect on the nephropathy risk, eGFR status or ERFD outcome among patients with type two diabetes in Taiwan. Conclusion: Our findings indicate that larger studies would be necessary to clearly ascertain the effects of individual genetic variants and further investigation is also required to identify other genetic pathways underlying DN.